2010
DOI: 10.1088/0953-8984/22/26/265005
|View full text |Cite
|
Sign up to set email alerts
|

A density functional study of the adsorption of methane-thiol on the (111) surfaces of the Ni-group metals: I. Molecular and dissociative adsorption

Abstract: The molecular and dissociative adsorption of methane-thiol (CH(3)SH) in the high-coverage limit on the (111) surfaces of the Ni-group metals has been investigated using ab initio density functional techniques. In molecular form, methane-thiol is bound to the surface only by weak polarization-induced forces in a slightly asymmetric configuration with the C-S axis tilted by 35-60° relative to the surface normal. On Ni and Pd surfaces the S atom occupies a position close to a bridge site; on Pt it is located clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 86 publications
4
24
0
1
Order By: Relevance
“…The LEED patterns of Figs. 2͑b͒ and 2͑d͒ are very similar to those reported by Domange and Oudar for Cu͑110͒ following exposure to H 2 S. 29 Considering the simple structure of methanethiol, and that the highest occupied to lowest unoccupied molecular orbital gap is ϳ4.5-5.5 eV, 30,31 it is likely that RAS is probing the thiolate/Cu͑110͒ interface and that the methyl group has relatively little effect on the RAS signal. To evaluate this view, the methyl group can be removed by heating: Carley et al 13,14 have shown that heating CH 3 S / Cu͑110͒ surfaces above 400 K results in the decomposition of the adsorbate to leave only a chemisorbed S adlayer, which appears to be identical to that prepared from the exposure of clean Cu͑110͒ to H 2 S. 14 RAS is sensitive to both the bonding interaction and the spatial arrangement of adsorbates at the interface and so to evaluate the contribution from the methyl group, and any difference between thiolate-Cu and S-Cu bonding, the surface structure following the heating process must be similar to that before.…”
Section: A Methanethiol/cu(110)supporting
confidence: 79%
“…The LEED patterns of Figs. 2͑b͒ and 2͑d͒ are very similar to those reported by Domange and Oudar for Cu͑110͒ following exposure to H 2 S. 29 Considering the simple structure of methanethiol, and that the highest occupied to lowest unoccupied molecular orbital gap is ϳ4.5-5.5 eV, 30,31 it is likely that RAS is probing the thiolate/Cu͑110͒ interface and that the methyl group has relatively little effect on the RAS signal. To evaluate this view, the methyl group can be removed by heating: Carley et al 13,14 have shown that heating CH 3 S / Cu͑110͒ surfaces above 400 K results in the decomposition of the adsorbate to leave only a chemisorbed S adlayer, which appears to be identical to that prepared from the exposure of clean Cu͑110͒ to H 2 S. 14 RAS is sensitive to both the bonding interaction and the spatial arrangement of adsorbates at the interface and so to evaluate the contribution from the methyl group, and any difference between thiolate-Cu and S-Cu bonding, the surface structure following the heating process must be similar to that before.…”
Section: A Methanethiol/cu(110)supporting
confidence: 79%
“…The Born charges can be used to obtain the polarisation derivatives along the mode eigenvectors using the relationship:where A is a generic physical quantity, and the sum runs over the n a atoms in the primitive cell. I IR is calculated as: 47,48 The three components of the dipole derivative in eqn (7) are summed to give the overall intensity.…”
Section: Ab Initio Lattice-dynamics Calculationsmentioning
confidence: 99%
“…Concerning the route i) in the case of gold reconstructed surface [48], the S-H dissociation takes place through a transition state of 0.32 eV. For methanethiol dense adsorption (33 R30 pattern) DFT calculations [46] give no barrier for Ni, 0.18 eV for Pd and 0.61 eV for Pt. It is thus expected that in the case of silver, higher coverage and irregular surfaces lead to a barrier lower than 0.98 eV making dissociation easier.…”
Section: Accepted Manuscriptmentioning
confidence: 99%